2018
DOI: 10.31616/asj.2018.12.5.810
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Clinical Evaluation of Enhanced Unilateral Open-Door Laminoplasty Using Titanium Mesh

Abstract: Study DesignObservational, cross-sectional study.PurposeThe purpose of this study was to evaluate the clinical efficacy and safety profile of open-door laminoplasty (ODL) using titanium mesh.Overview of LiteratureThe most appropriate surgical management of degenerative spine disorders, particularly ossification of the posterior longitudinal ligament, remains controversial and continues unabated in the neurosurgical community. However, recently, ODL has become popular among surgeons. Many modifications have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…To our knowledge, this is the first study to have directly compared the operative time between the use of TP and HA spacers in open-door laminoplasty. Previous studies have reported an operative time of 112–160 min for HA spacers [1921], compared to 90–181 min for TP spacers [2226]. However, as these were single-arm descriptive studies of either procedure without direct comparison, the benefit of TP spacers on operative time could not be confirmed.…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, this is the first study to have directly compared the operative time between the use of TP and HA spacers in open-door laminoplasty. Previous studies have reported an operative time of 112–160 min for HA spacers [1921], compared to 90–181 min for TP spacers [2226]. However, as these were single-arm descriptive studies of either procedure without direct comparison, the benefit of TP spacers on operative time could not be confirmed.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, cervical laminoplasty with titanium mesh has also been reported recently as a novel and safe technique. 15 Regarding the use of titanium mesh in the developing spines of pediatric patients, in children older than 10 years of age, sacral instrumentation with screws and rods has been reported as a standard procedure with an instrumentation failure rate as low as 1.3%. 7 In a younger child, the spinal canal grows to approximately 90% of its definitive size by age 3-5 years.…”
Section: Discussionmentioning
confidence: 99%